Determinasi Loyalitas Nasabah Bank Central Asia: Perspektif Kualitas Pelayanan, Kepercayaan dan Kepuasan - Salsabilla Rahma; Handayani; Eka Patriya; Andriansyah Latif (Forum Kerjasama Pendidikan Tinggi, 2024)
The objective of this study is to analyze the influence of service quality, trust, and satisfaction on customer loyalty at Bank BCA. The research employs qualitative primary data, with tests including validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, R coefficient of determination, t-test, and F-test. Data for this study were gathered using a questionnaire, with valid responses collected from 100 respondents. The sampling method used is non-probability sampling with purposive sampling technique. The analytical tool used is multiple linear regression with SPSS version 22. The study results show that, in partial tests, service quality has a significance value of 0.027 < 0.05, trust has a significance value of 0.030 < 0.05, and satisfaction has a significance value of 0.000 < 0.05. Simultaneously, the test yields a significance value of 0.000 < 0.05, indicating that both partial and simultaneous tests have a significant effect on customer loyalty at Bank BCA KCU Bekasi Barat.